2022
DOI: 10.3389/fnins.2022.831761
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation in Functional Dyspepsia: Bystander Becoming the Suspect

Abstract: Disorders of gut-brain interaction (DGBI), formerly termed functional gastrointestinal disorders (FGID), are highly prevalent although exact pathophysiological mechanisms remain unclear. Intestinal immune activation has been recognized, but increasing evidence supports a pivotal role for an active inflammatory state in these disorders. In functional dyspepsia (FD), marked eosinophil and mast cell infiltration has been repeatedly demonstrated and associations with symptoms emphasize the relevance of an eosinoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 201 publications
(266 reference statements)
1
14
0
7
Order By: Relevance
“…In contrast, few studies have demonstrated changes in stomach immune cell profiles, none of which are associated with symptoms of FD ( Futagami et al, 2010 ; Li et al, 2010 ; Pasricha et al, 2021 ), confirming that dyspeptic symptoms do not directly correlate with gastric pathophysiology. Accordingly, this further strengthens the notion that the duodenum is likely to be the key pathogenic organ for FD in that impaired duodenogastric communication is induced by duodenal abnormalities therefore generating FD symptoms ( Vanheel and Farré, 2013 ; Wauters et al, 2020a ; Ceulemans et al, 2022 ). Furthermore, increased mast cells and degranulation was found in the duodenum of FD patients in addition to the eosinophilic infiltration ( Vanheel et al, 2014 ; Cirillo et al, 2015 ; Taki et al, 2019 ), although these findings were not always consistent ( Tanaka et al, 2016 ; Puthanmadhom Narayanan et al, 2021 ), nevertheless substantiating the concept of an eosinophil-mast-cell axis ( Wechsler et al, 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, few studies have demonstrated changes in stomach immune cell profiles, none of which are associated with symptoms of FD ( Futagami et al, 2010 ; Li et al, 2010 ; Pasricha et al, 2021 ), confirming that dyspeptic symptoms do not directly correlate with gastric pathophysiology. Accordingly, this further strengthens the notion that the duodenum is likely to be the key pathogenic organ for FD in that impaired duodenogastric communication is induced by duodenal abnormalities therefore generating FD symptoms ( Vanheel and Farré, 2013 ; Wauters et al, 2020a ; Ceulemans et al, 2022 ). Furthermore, increased mast cells and degranulation was found in the duodenum of FD patients in addition to the eosinophilic infiltration ( Vanheel et al, 2014 ; Cirillo et al, 2015 ; Taki et al, 2019 ), although these findings were not always consistent ( Tanaka et al, 2016 ; Puthanmadhom Narayanan et al, 2021 ), nevertheless substantiating the concept of an eosinophil-mast-cell axis ( Wechsler et al, 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…Since then, several groups reported similar findings and a meta-analysis confirmed increased T-cells in the lamina propria of the rectosigmoid 57. In contrast, gastroduodenal lymphocyte infiltration, including intra-epithelial lymphocyte counts, does not come up as a consistent feature of FD,58 59 even if two small studies reported elevated CD8+T cell counts and aggregates in postinfectious FD 60 61. Peripheral blood lymphocytes expressing gut-homing markers were increased in FD40 and IBS 62–64.…”
Section: Immune Activationmentioning
confidence: 86%
“…Moreover, as discussed above, IBS supernatant-induced hyperreactivity of neurons which could be blocked by histamine receptor H1 antagonists and protease inhibitors, underscoring the importance of mast cell derived soluble mediators in neuronal hyperreactivity 32 33 47. The role of mast cells in FD is less established, although a few studies have shown increased duodenal mast cell counts 59 69. Mast cell activation in FD is suggested by a study using electron microscopy showing more heterogeneous granules in duodenal mast cells in FD and evidence of increased release of histamine and tryptase from gastric biopsies 36 70.…”
Section: Immune Activationmentioning
confidence: 96%
See 2 more Smart Citations